Tanggung Jawab Moral Ilmuwan Dalam Perspektif Aksiologi Ilmu - Monika Adela; Mardi Widodo (GRM Academic Press, 2026)
The development of science and technology has brought significant changes to various aspects of human life. While scientific progress offers numerous benefits, it also raises complex ethical issues when science is developed and applied without moral considerations. Therefore, discussing the moral responsibility of scientists becomes essential, particularly from the perspective of the axiology of science. This article aims to examine how the axiology of science views the role and moral responsibility of scientists in directing scientific knowledge toward humanistic values. This study employs a qualitative approach using a literature review method, analyzing relevant books and scholarly articles in the fields of philosophy of science and ethics. The findings indicate that the axiology of science emphasizes values, purposes, and benefits as fundamental elements of scientific practice. Scientists are responsible not only for the validity of scientific knowledge but also for its social, humanitarian, and environmental impacts. Consequently, the integration of ethical values into scientific activities is imperative to ensure that science does not lose its direction and can function as a means of improving the quality of human life in a fair and sustainable manner.